A new approximate fast method of computing the scattering from multilayer rough surfaces based on the Kirchhoff approximation. Issue 2 (2nd February 2017) - Tian, Jiasheng; Tong, Jian; Shi, Jian; Gui, Liangqi
Abstract: In this paper a new approximate fast method of calculating the bistatic‐scattering coefficients of a multilayer structure with random rough interfaces was presented based on the Kirchhoff Approximation (KA) and the electromagnetic theory of stratified media. First, the electromagnetic scattering from a Gauss rough metal or dielectric surface was calculated by KA method and method of moment (MOM), and the effectiveness of KA method was confirmed and verified. Second, a new approximate fast method was presented to calculate electromagnetic scattering from a multilayer‐random‐rough surface based on electromagnetic reflection from multilayer parallel surfaces and KA. The calculated results by the new method were in good agreements with those by MOM, especially near the specular point. Finally, a comparison of the new method and MOM was carried out in consuming computing time, memory resources, and complexity. The comparison indicated that the new approximate method was faster by about 30–150 times than MOM. The new approximate fast method could avoid a large matrix inversion and greatly reduce the computation time and memory resources and thus improve the computational efficiency. It was an effective approximation fast analyzing method of electromagnetic scattering from multilayer rough surfaces. Key Points: A new approximate fast method of calculating the scattering from random rough interfaces is presented Combing electromagnetic reflection from multilayer parallel surfaces and KA The new approximate fast method is faster by 30–150 times than MOM